Variability and repeatability of quantitative, fourier-domain optical coherence tomography doppler blood flow in young and elderly healthy subjects - Tayyari, Faryan Tayyari; Yusof, Firdaus; Vymyslicky, Michal; Tan, Ou; Huang, David; Flanagan, John G. Flanagan; Hudson, Christopher (The Association for Research in Vision and Ophthalmology, Inc., 2014)
Purpose. The purpose of this study was to determine the within-session variability and between-session repeatability of spectral Fourier-domain optical coherence tomography (Doppler FD-OCT) Doppler retinal blood flow measurements in young and elderly subjects.